The United States as a Creditor Nation - Bullock, C. J. (The Review of Economics and Statistics, 1932)
BETWEEN I 9 I 9 and I92I the REVIEW OF ECONOMIC STATISTICS published several studies of the balance of payments of the United States, which pointed to the conclusion that the War had made us a nation. We assumed that this term, which was well established in economic literature, had a definite and generally accepted meaning; and we did not undertake to define it. In recent years it has become clear that we should have defined the term with care, and that the United States has not become a in the sense that we intended at that time. Whatever their origin, and this is not important for present purposes, the terms and became well established in economic literature by the end of the nineteenth century. England was a nation. From interest on foreign investments, earnings of ships, and various other items in her annual accounts she had a large balance in her favor, which enabled her to import commodities greatly in excess of her exports and so to pay for a large unfavorable balance in such accounts. Upon the other hand, the United States, with a large balance against her on account of the invisible items, exported commodities greatly in excess of her commodity imports, and thereby paid her debts. Clearly the term had reference to a country's position on account of the invisible items in her balance of payments, and the visible proof of that position was the existence of an excess of commodity imports. If usage had been guided wholly by the idea of an annual reckoning of a country's international accounts, the terms might as well have been applied differently; and a country with a sufficient excess of commodity exports might just as well have been called a country. But interest on foreign investments bulked so large among the invisible items that a country, like England, that had long exported capital was in the old and familiar sense the of the countries to which her capital had flowed. Therefore it was natural that the country with a balance of invisible items should be called the nation, and the country showing a surplus of commodity exports should be termed the debtor. All this, of course, related to transactions on income account, and disregarded capital transactions which in any year might temporarily make a country a debtor if it exported an unusual amount of capital. Thus the richest country might be temporarily in debt, and export gold to balance her total accounts in any year; while at the same time, and for just the opposite reason, the poorest debtor country might temporarily become a and receive gold imports. Those who follow the exchanges from month to month, or try to determine a country's position at the end of every year, must of course consider capital as well as income transactions. But a country's normal position as debtor or is not determined by the capital transactions of any year, but by those on income account which are the ultimate determinants of a country's international position. If, therefore, economists are to use the terms and country, they should disregard capital transactions and consider only a country's normal position on income account. According to the older usage, therefore, a country was one which in any normal year had a balance in its favor on account of the invisible items entering into its foreign transactions on income account. Visible items might have been considered instead of invisible; but they were not, and this was probably because the countries having favorable balances of the invisible items were also the countries that made foreign loans or investments and therefore were creditors in the old-fashioned and legal sense of the word. This we believe to be a correct account of the term creditor nation as it was used prior to the War. Obviously a may be a debtor on account of the invisible items but so largely a on account of the visible items (commodity exports) that its total income account for a period of years shows a balance in its favor. Should such a be classified as a debtor? Obviously not, unless the term is going to be used in a technical sense not conducive to scientific insight and con-